Needs analysis for designing and developing an efl teaching-speaking module for the unique linguistic tapestry of Chinese business english undergraduates - Ke Hu; Asmaa AlSaqqaf (Problems Of education In the 21stcentury, 2024)
Developing effective oral business English (OBE) curricula requires clearly understanding student needs. This study evaluated the speaking needs of Chinese English as a Foreign Language (EFL) undergraduates majoring in business English for specific purposes (ESP), aiming to inform the design of a teaching module that bridges the gap between current speaking abilities and the escalating demand for advanced communication skills in business contexts. A needs analysis questionnaire, reflecting the first phase of the ADDIE model (analysis, design, development, implementation, evaluation), was administered to 398 randomly selected participants using a quantitative, cross-sectional survey design. Results revealed that while students struggle with speaking errors and lack communication confidence, they favor interactive activities such as presentations, discussions, and role-plays. Concerns about current OBE pedagogy and materials highlight a need for more collaborative learning and teacher support. Statistical analysis using independent-samples t-test and one-way ANOVA showed no significant differences in speaking needs based on gender, age, years of English study, or English proficiency. However, a significant difference was reported between fourth-year and third-year students. This study offers some insights for developing more effective interventions to address the specific needs of Chinese business English undergraduates in Chinese ESP education.